A model for Joint Venture amongst community forest enterprises (CFEs) - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
The tool has been under piloting now for about 12 Months in three community forests in the Center region of Cameroon. Analysis of implementation and write up is ongoing.